Efficacy and Safety of Intravenous Thrombolysis on Acute Branch Atheromatous Disease: A Retrospective Case–Control Study - Wu, Xiangbo; Liu, Yang; Nie, Chuang; Kang, Zhiming; Wang, Qunfeng; Sun, Dong; Li, Huagang; Liu, Yumin; Mei, Bin (Frontiers in Neurology, 2020)
Background: Poor outcome and early neurological deterioration (END) frequently occured in single subcortical infarction due to branch atheromatous disease (BAD). we evaluated whether intravenous thrombolysis (IVT) plus usual care could improve functional outcome and prevent END comparing to usual care alone in single subcortical infarction related to BAD. Methods: This study analyzed retrospectively data from consecutive patients with BAD-related stroke from January 2015 to August 2019. Those patients who met the inclusion criteria were divided into two groups according to whether received IVT or not : tPA group and No-tPA group. The primary outcome was the adjusted common odds ratio for categorical shift in the distribution of the modified Rankin Scale scores (mRS) at 3 months by fitting an ordinal logistic regression, adjusted for severity of symptoms. Results: Of 618 patients with BAD-related stroke during study period, 129 patients (88 of 129 [68.2%] men) with a mean (SD) age of 62(13) years were finally enrolled in our study: 50 in the tPA group and 79 in the non-tPA group. The tPA group had a higher NIHSS score on admission(median,7 points vs 4 points; P＜0.001), lower NIHSS score at discharge (median, 2 points vs 4 points; P=0.005), and shorter hospital stays (median, 9 days vs 11 days; P=0.004) than control group. An ordinal logistic regression demonstrated a significant shift in mRS scores at 3 months in favor of intravenous thrombolysis; adjusted common odds ratio (OR) 3.88 (95% confidence interval [CI], 1.87-5.89). Favorable outcome (mRS, 0-1 points) was observed in 28 of 50 patients (56.0%) in the tPA group compared with 37 of 79 patients (46.8%) in the non-tPA group(adjusted OR, 4.29; 95%CI, 1.64-11.28). The incidence of early neurological deterioration in the tPA group was much lower than that of the non-tPA group (adjusted OR, 0.33; 95% CI, 0.13-0.84). Conclusion: Intravenous thrombolysis with tPA can effectively improve outcome and prevent early neurological deterioration in patients with BAD-related stroke.